2023
DOI: 10.4103/1673-5374.379016
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress and future directions of the research on nanoplastic-induced neurotoxicity

Abstract: Many types of plastic products, including polystyrene, have long been used in commercial and industrial applications. Microplastics and nanoplastics, plastic particles derived from these plastic products, are emerging as environmental pollutants that can pose health risks to a wide variety of living organisms, including humans. However, it is not well understood how microplastics and nanoplastics affect cellular functions and induce stress responses. Humans can be exposed to polystyrene-microplastics and polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The GO and KEGG analyses showed the entire process of NPs’ cellular internalization and their behavior in the cell. After entering the cell by endocytosis, NPs accumulated in endosomes and then entered the lysosome for degradation or exited the cell directly as exosomes. , NPs could be released into the cytoplasm or other organelles by endosomal escape or lysosomal dysfunction, thereby affecting normal cellular function such as metabolism and protein processing in the endoplasmic reticulum (ER). , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GO and KEGG analyses showed the entire process of NPs’ cellular internalization and their behavior in the cell. After entering the cell by endocytosis, NPs accumulated in endosomes and then entered the lysosome for degradation or exited the cell directly as exosomes. , NPs could be released into the cytoplasm or other organelles by endosomal escape or lysosomal dysfunction, thereby affecting normal cellular function such as metabolism and protein processing in the endoplasmic reticulum (ER). , …”
Section: Resultsmentioning
confidence: 99%
“…A recent study also reported the absence of significant toxicity toward THP-1 cells at low doses of NPs. NPs are more harmful than MPs because the biological effect is caused by MNPs entering the cell. , Therefore, 100 nm NPs at a concentration of 100 μg/mL were chosen for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Given that nanoplastics can directly penetrate the blood-brain barrier (BBB) and accumulate in the central nervous system (CNS), [16][17] great concerns about their potential effects on neuronal activities and brain functions and possible link to neurodegenerative diseases as well are therefore rapidly growing. [18][19] Recent studies suggest that nanoplastics could affect the basal levels of neurotransmitters in vivo [20][21] and learning/memory abilities of mice. [22] Vesicles are the smallest organelles executing neurotransmission functions by fusing with presynaptic membranes and releasing neurotransmitters into the synaptic cleft to elicit postsynaptic depolarization and action potential propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that nanoplastics can directly penetrate the blood–brain barrier (BBB) and accumulate in the central nervous system (CNS), [16–17] great concerns about their potential effects on neuronal activities and brain functions and possible link to neurodegenerative diseases as well are therefore rapidly growing [18–19] . Recent studies suggest that nanoplastics could affect the basal levels of neurotransmitters in vivo [20–21] and learning/memory abilities of mice [22] .…”
Section: Introductionmentioning
confidence: 99%